Kinerja Teknologi Reverse Osmosis AROFAH dalam Pengolahan Air Permukaan sebagai Sumber Air Minumdi Daerah Bencana - Panji Mahesa Monanov; Setijo Bismo (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
The provision of safe drinking water in post-disaster conditions is a critical necessity. This study aims to evaluate the performance of the basic prototype of the AROFAH Machine based on Reverse Osmosis (RO) technology, designed to treat various sources of surface water into potable water. The system consists of pre-treatment using polypropylene (PP) filters, granular activated carbon (GAC), carbon block (CTO), and a Polyamide Thin Film Composite (TFC) RO membrane. Testing was conducted using surface water at the DTK Building, lake water, and river water on the UI Depok campus, with flow restrictor variations of 400 and 550 mL/min. The results showed permeate TDS of 2–15 mg/L from feedwater TDS of 91–170 mg/L, with removal efficiency of 93–99%. The permeate flow rate remained relatively stable at 410–430 mL/min during 120 minutes of operation. All permeate samples met microbiological requirements, with E. coli and Total Coliform at 0 CFU/100 mL. The designed system requires only about 36 W of power, making it potentially suitable as a portable drinking water unit for disaster-affected areas.